OPTIMAL CAPITAL STRUCTURE OF PT ADHI KARYA (PERSERO) TBK - Salsabila, Fania
Construction industry contributes significantly to Indonesia’s Gross Domestic Product (GDP) in 2021, ranking fourth among other industries. PT Adhi Karya Tbk is one of construction stateowned enterprises in Indonesia. Due to the Covid-19 pandemic situation, the firm experienced a